Extrajudicial Killings over the Drug War in the Philippines under the ICC Jurisdiction - Gunawan, Yordan; Permana, Vensky Ghaniiyyu Putri (Jurnal Suara Hukum, 2024)
Extrajudicial killings in the Philippines have escalated, resulting in severe human rights violations exacerbated by the enforcement of drug war policies, which have led to numerous deaths without due legal process. These killings constitute serious crimes falling within the jurisdiction of the International Criminal Court (ICC). This paper examines how the ICC can serve as an international mechanism for addressing extrajudicial executions in the Philippines' drug war. Employing normative legal research methodology, the study utilizes legal sources focused on normative law as primary data. The ICC, functioning as a permanent court, is mandated to prosecute individuals responsible for international crimes under the Rome Statute. The findings confirm that extrajudicial killings in the Philippines qualify as international crimes, thus within the ICC's purview. Consequently, the ICC's involvement should not be construed as a challenge to national sovereignty but rather as a catalyst for strengthening global criminal justice frameworks. By holding perpetrators accountable, the ICC can stimulate the development of national criminal justice systems worldwide and encourage the enactment of domestic laws addressing egregious human rights violations and breaches of international humanitarian law. This role underscores the ICC's mission to promote universal ideals and ensure justice for victims of grave international offenses.